IMPLEMENTASI PROGRAM SEKOLAH LIMA HARI (PS5H) DI SMK TERHADAP KESIAPAN KERJA SISWA - Eko Saputro; Suharno Suharno; Budi Harjanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
The objectives of this research are 1) to know the correlation between the implementation of intracuricular activities in the five-days school program at Vocational High Schools toward students’ work readiness, 2) to know the correlation between the implementation of co-curricular activities in five-days school program at Vocational High School toward students’ work readiness, 3) to know the correlation between implementation of both activities (intracuricular and co-curricular) or five-days school program in Vocational High School toward students’ work readiness. This research was conducted  in Vocational High School State 5 Surakarta. This research used a quantitative approach with a descriptive correlational research design because it is aimed to see the level of correlation between independent and dependent variables. Data collection techniques used in this research is questionnaire. Data testing techniques using simple correlation analysis techniques and multiple correlation using the SPSS application program version 25.0. Based on thefinding of the research , it can be concluded that 1) there is a positive correlation and a significant correlation between the implementation of intracuricular activities in five-days school program toward students’ work readiness as proved by the value of rcount = 0.422 > rtable = 0.174 and the significance value of 0.00 < 0.05, 2) based on that there is a positive correlation and a significant correlation between the implementation of co-curricular activities in five-days school program toward students’ work readiness as proved by value of  rcount = 0.622 > rtable = 0.174 and the significance value is 0.00 < 0.05, 3) there is a positive correlation and a significant correlation between both activities ;intracuricular and co-curricular or the five-days school program in Vocational High School toward the students’ work readiness as proved by the value of Fcount = 40.123 > Ftable = 3.07 and the significance value of 0.00 < 0.05. The finding of this research can be selected as a consideration and suggestions for the government in determining and deciding the policy.